Kajian Tema secara Persepsi Visual pada Museum Angkut di Kota Batu, Jawa Timur - Aprilia, Santi (Intra, 2015)
This research is conducted to discover visitorsâ visual perception on applied theme of every zone in Museum Angkut. Museum Angkut has many zones, but the ones that will be researched are Batavia and Pecinan zone, Gangster Town and Broadway Street zone, Italy zone, Paris zone, Germany zone, London Street zone, Buckingham Palace zone, Las Vegas zone, and Hollywood zone. The method applied in this research is inductive qualitative with descriptive approach supported by in-depth interview data gathering technique, by using purposive sampling technique with 10 correspondents that were divided into two groups: five correspondents who have no interior design academic background and another five who have interior design academic background. The result found that visual perception caught by correspondents who have no interior design academic background is different from those who have interior design academic background in terms of shape and space variables. The research discovered that visitors could recognize the applied theme more through shape variable. Correspondents recognized shape variables based on symbols, writings, and transportationsâ display, while space variables were acknowledged through circulation and themeâs relevance.